2001
DOI: 10.1002/ijc.10114
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E6‐enhanced susceptibility to apoptosis induced by TNF in A2780 human ovarian cancer cell line

Abstract: In our study, we show that expression of HPV-16 E6 sensitizes TNF-induced cytotoxicity of human ovarian cancer cell line A2780. This effect is not related to a different number of TNF receptors present on cell membrane. The major induction of massive apoptosis induced by TNF is not p53-and p21waf-1 -dependent but it is principally related to NF-B inhibition in A2780/E6 cells. Consistently to NF-B inhibition a rapidly release of cytochrome c and severe induction of DNA fragmentation are seen in A2780/E6 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…In a previous report, Yu et al (1997) found that sensitivity of different human cell lines to death decreases when E6 from HR HPV is expressed. Nevertheless, a very recent study showed that the expression of HPV 16 E6 sensitizes TNF-induced cytotoxicity of human ovarian cancer cell lines and this effect is not p53-dependent but mediated through an inhibition in activating NF-KB activities (Vikhanskaya et al, 2002), whilst another study demonstrated that HPV 16 E6 binding to (TNF) R1 protects cells from TNF-induced apoptosis (Filippova et al, 2002). Similar to the findings with E6, the E7 protein of HPV 16 can either induce or prevent apoptotic cell death, depending on the recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, Yu et al (1997) found that sensitivity of different human cell lines to death decreases when E6 from HR HPV is expressed. Nevertheless, a very recent study showed that the expression of HPV 16 E6 sensitizes TNF-induced cytotoxicity of human ovarian cancer cell lines and this effect is not p53-dependent but mediated through an inhibition in activating NF-KB activities (Vikhanskaya et al, 2002), whilst another study demonstrated that HPV 16 E6 binding to (TNF) R1 protects cells from TNF-induced apoptosis (Filippova et al, 2002). Similar to the findings with E6, the E7 protein of HPV 16 can either induce or prevent apoptotic cell death, depending on the recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…31 In brief, MSTO-211H cells were harvested by gently scraping and were incubated in a buffer containing 220 nM mannitol and 60 mM sucrose on ice for 30 minutes. Then, cells were broken in a Dounce homogenizer by 70 gentle strokes of a type B pestle.…”
Section: Preparation Of Mitochondria-free Cytosolic Extracts and Wholmentioning
confidence: 99%
“…Nucleic extracts were prepared according to the method described by Vikhanskaya et al 31 Briefly, 5 ϫ 10 5 cells were collected, washed in PBS, and pelleted. Pellets were resuspended in 400 mL of hypotonic buffer (20 mM N-2-hydroxyethyl piperazine-NЈ-2-ethane sulphonate [HEPES], pH 7.9; 10 mM KCl; 0. ; 2% .5 mg/mL proteinase K, mg/mL proteinase K n was washed from fil n was washed from H 10, and the DNA was 10, and the DNA was onium hydroxide-EDT onium hydroxide-ED at a flow rate of t a flow rate of 3-hour inte hour in…”
Section: Gel Mobility-shift Assaymentioning
confidence: 99%
“…Work by our laboratory and others has suggested that the papillomavirus E6 protein may function in immune evasion by modifying an infected cell's response to such apoptotic stimuli (reviewed by Finzer et al 33 ). Paradoxically, while some studies report that E6 sensitizes cells to apoptosis induced by TNF, 34,35 others report that it protects cells from TNF. 16,36 The apparent contradiction regarding the effect of E6 on a cell's response to TNF is currently unresolved and suggests that the effect of E6 on a given cell will depend on the cell type, cellular environment, factors associated with the expression of E6 and/or on the experimental approaches used, although no mechanistic basis for this has been proposed.…”
Section: Introductionmentioning
confidence: 99%